THE EFFECT OF EARNING PERSISTENCE TOWARD FINANCIAL PERFORMANCE OF LISTED BANKS IN INDONESIA STOCK EXCHANGE - Anggi Choirina; Nurmala Ahmar (Universitas Hayam Wuruk Perbanas, 2013)
Getting information about earnings is important for the parties who are interested in investmentin a company. The purpose of this study is to examine the earnings persistence effecttoward performance of Indonesian bank listed in Bursa Efek Indonesia (BEI), with company’ssize as control variable. This study use a sample of Indonesian bank listed in BEIfrom 2007 to 2010. Bank’s financial performance is measured using seven indicators, namelyCash and Bank to Total Deposits (CBTD), Loan to Total Deposits (LTTD), Equity to TotalAsset (ETTA), Operating Profit Margin (OPM), Net Profit Margin (NPM), Return on Equity(ROE), and Return on Investment (ROI) as dependent variables. Earnings persistence as theindependent variable is the regression coefficient of Earning per Share at one year before t(EPSt-1) when it regressed toward EPSt. Bank size is used as control variable. The result ofregression model indicates that earnings persistence influence the performance of Indonesianbank listed in BEI. Of the seven measures of bank performance, only LTTD and ROE are notinfluenced by earnings persistence.